Dai-Zong-Fang, A Traditional Chinese Herbal Formula, Ameliorates Insulin Resistance in db/db Mice - Zhu, Lili; Zhu, Xiaoyun; Sun, Guibo; Meng, Xiangbao; Wang, Min; Cui, Hanming; Wang, Jialong; Zhai, Yadong; Yang, Ke; Tang, Yang; Sun, Xiaobo; Liu, Ximing (Frontiers in Physiology, 2018)
Intricate health problems, such as insulin resistance (IR) and its associated diseases, call for multi-targeted therapies with few side effects. Based on traditional Chinese medicine (TCM), Dai-Zong-Fang (DZF) is an herbal formula mainly composed of Rhizoma Coptidis (Huanglian) and Fructus Aurantii Immaturus (Zhishi), of which berberine and narigin are the main constituents. Though DZF has been clinically used for treatment of IR and metabolic syndrome for decades, its mechanism in vivo remains unknown. In the present study, we observed that both DZF and metformin, the first-line drug for type 2 diabetes, ameliorated insulin resistance with significant improvement of oral glucose tolerance test (OGTT) and homeostasis model assessment of IR (HOMA-IR) level in diabetic C57BL/Ksj-Lepr db-/- (db/db) mice. Low-density lipoprotein cholesterol (LDL-C) and fatty acids (FAs) also decreased in the blood. Higher dose of DZF (1 g•kg-1), but not metformin (0.25 g•kg-1), alleviated hepatic steatosis with reduced liver weight and hepatic lipid accumulation and provided protection from hepatic injury with lower alanine aminotransferase and aspartate aminotransferase and increased hepatic superoxide dismutase activity in db/db mice. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) showed a decrease in FA synthase gene (Fasn) and an increase in FA oxidation gene Ppara expression. Western blot demonstrated that both DZF and metformin activated 5ʹ AMP-activated protein kinase (AMPK) but inhibited Notch intracellular domain (NICD) and Hairy/enhancer-of-split 1 (Hes1) of Notch signaling pathway in the liver. DZF also dramatically improved the ultrastructure of skeletal muscles, AMPK phosphorylation, and GLUT4 translocation. DZF also promoted FA transport and oxidation with Cd36 and Cpt1b up-regulation in the skeletal muscle. In conclusion, DZF improves insulin sensitivity by reducing hepatic lipids through AMPK activation and Notch signal pathway inhibition and enhancing energy metabolism in the skeletal muscle via AMPK. This study provides insights into the treatment of complex conditions, such as IR, where TCM herbal formulas exert multipronged effects through correlating pathways.